A Novel Range-Extended Strategy for Fuel Cell/Battery Electric Vehicles. (5th July 2015) - Hwang, Jenn-Jiang; Hu, Jia-Sheng; Lin, Chih-Hong
Abstract : The range-extended electric vehicle is proposed to improve the range anxiety drivers have of electric vehicles. Conventionally, a gasoline/diesel generator increases the range of an electric vehicle. Due to the zero-CO2 emission stipulations, utilizing fuel cells as generators raises concerns in society. This paper presents a novel charging strategy for fuel cell/battery electric vehicles. In comparison to the conventional switch control, a fuzzy control approach is employed to enhance the battery's state of charge (SOC). This approach improves the quick loss problem of the system's SOC and thus can achieve an extended driving range. Smooth steering experience and range extension are the main indexes for development of fuzzy rules, which are mainly based on the energy management in the urban driving model. Evaluation of the entire control system is performed by simulation, which demonstrates its effectiveness and feasibility.